BENTUK PENYAJIAN KESENIAN BARUDA PADA ACARA KHATAM AL-QURAN DI JORONG LADANG LAWEH KECAMATAN LINTAU BUO UTARA KABUPATEN TANAH DATAR - Lastri Elita; Marzam Marzam; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2016)
Purposed of this research is to decribe forms presentation about art of Baruda on khatam Al-quran in Ladang laweh, Lintau Buo Utara, Tanah Datar. This research useg qualitative forms with descriptive method. An object of research is: presentation of Baruda on khatam Al-quran in Ladang Laweh, Lintau Buo Utara, Tanah Datar. Data collection is doing by library studied, observation, inteview, video record, voice record dan photography. Processing data useg by qualitative analysis. From an analyzing found that presentation of Baruda on khatam Al-quran in Ladang Laweh, Lintau Buo Utara, Tanah Datar consist of: amount of nine players byarrack forms, useg musical instrument of Rebana, a song to accompanied Rebana was read by Barzanji, position players Baruda is in back part of line khatam Al-quran. Costume useg an uniform like a moeslim clothes or batik clothes.